2024
DOI: 10.2174/1570179420666230607124949
|View full text |Cite
|
Sign up to set email alerts
|

The Golden Spice for Life: Turmeric with the Pharmacological Benefits of Curcuminoids Components, Including Curcumin, Bisdemethoxycurcumin, and Demethoxycurcumins

Abstract: Background: Turmeric (Curcuma longa L.), belonging to the Zingiberaceae family, is a perennial rhizomatous plant of tropical and subtropical regions. The three major chemical components responsible for the biological activities of turmeric are curcumin, demethoxycurcumin, and bisdemethoxycurcumin. Method: The literature search included review articles, analytical studies, randomized control experiments, and observations, which have been gathered from various sources, such as Scopus, Google Scholar, PubMed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 295 publications
0
6
0
Order By: Relevance
“…Amino acids for the production of biostimulants are derived by chemical synthesis from plant proteins such as soybean, corn, algae, corn, etc., as well as from animal proteins by enzymatic and chemical hydrolysis [ 57 , 58 , 59 , 60 , 61 , 62 ]. Amino acids act as vital molecules with various physiological roles [ 63 ] and play an important function in seed germination [ 64 , 65 ], and under salinity stress, they can behave as osmolytes, which can promote stomatal opening control, transport regulation, enzyme activation, heavy metals detoxification, redox homeostasis maintenance, and gene expression [ 66 , 67 , 68 , 69 , 70 ].…”
Section: Amino Acidsmentioning
confidence: 99%
“…Amino acids for the production of biostimulants are derived by chemical synthesis from plant proteins such as soybean, corn, algae, corn, etc., as well as from animal proteins by enzymatic and chemical hydrolysis [ 57 , 58 , 59 , 60 , 61 , 62 ]. Amino acids act as vital molecules with various physiological roles [ 63 ] and play an important function in seed germination [ 64 , 65 ], and under salinity stress, they can behave as osmolytes, which can promote stomatal opening control, transport regulation, enzyme activation, heavy metals detoxification, redox homeostasis maintenance, and gene expression [ 66 , 67 , 68 , 69 , 70 ].…”
Section: Amino Acidsmentioning
confidence: 99%
“…Curcumin(Cur) , a potent compound derived from the subterranean rhizome of turmeric, possesses notable anticoagulant, anti-inflammatory, and neuroprotective properties ( SHAHRAJABIAN and SUN, 2023 ). In their study, Ye et al (Ye et al, 2021) observed that curcumin effectively suppresses the expression of Notch-1, curtails the excessive proliferation of microglia, and concurrently diminishes the levels of TNF-α and IL-1β in rats.…”
Section: The Mechanism Of Tcmhs Intervention In Microglia and Its Rel...mentioning
confidence: 99%
“…The equivalent to 5.7 g of turmeric powder used to prepare the salad dressing, as dissolved in ½ cup of oil and ¼ cup of vinegar, yields a final concentration of approximately 32 mg mL −1 , which is three-times higher than the highest concentration (10 mg mL −1 ) used in the current study. Thus, in addition to the well-documented beneficial properties of turmeric on consumer health [8], basic use as a food ingredient may have antimicrobial applications to mitigate the risks for foodborne pathogen contamination.…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
“…In addition to enhancing flavor and color in food products, turmeric has applications to support human health, such as through anti-inflammatory, anti-cancer, and antimicrobial effects [8]. For example, ethnopharmacological studies have reported turmeric use as a medical herb for knee osteoarthritis [9], radiodermatitis [10], and cancers [11].…”
Section: Introductionmentioning
confidence: 99%